Multiplatform mobile: post-COVID-19 patient management in Lima, Peru - Cano Lengua, Miguel Ángel (2022)
This research aims to develop a multiplatform mobile application for managing post-Covid-19 patients in a Lima Hospital. The research used the Dart programming language and the Flutter framework to construct the multiplatform mobile application; for the REST services, the PHP programming language and the Laravel framework were used. Finally, all the information is stored in the system. of relational database management, MySql. For the project's development, it was decided to use the Scrum methodology, which was divided into four Srtint. All the needs extracted from the user stories collected by post-Covid-19 patients and medical personnel were reflected. , obtaining as a final product the mobile application and the master manager; finally, three technology specialists and two health specialists used expert judgment to measure the results. As a result, high satisfaction of 88.4% in the criteria: usability, scalability, technology, feasibility, and innovation; in this way, the product is validated for use in a Hospital in Lima.